Tree frog adhesion biomimetics: opportunities for the development of new, smart adhesives that adhere under wet conditions. (10th June 2019) - Meng, Fandong; Liu, Quan; Wang, Xin; Tan, Di; Xue, Longjian; Barnes, W. Jon. P.
Abstract : Enlarged adhesive toe pads on the tip of each digit allow tree frogs to climb smooth vertical and overhanging surfaces, and are effective in generating reversible adhesion under both dry and wet conditions. In this review, we discuss the complexities of the structure of tree frog toe pads in relation to their function and review their biomimetic potential. Of particular importance are the (largely) hexagonal epithelial cells surrounded by deep channels that cover the surface of each toe pad and the array of nanopillars on their surface. Fluid secreted by the pads covers the surface of each pad, so the pads adhere by wet adhesion, involving both capillarity and viscosity-dependent forces. The fabrication and testing of toe pad mimics are challenging, but valuable both for testing hypotheses concerning tree frog toe pad function and for developing toe pad mimics. Initial mimics involved the fabrication of hexagonal pillars mimicking the toe pad epithelial structure. More recent ones additionally replicate the nanostructures on their surface. Finally we describe some of the biomimetic applications that have been developed from toe pad mimics, which include both bioinspired adhesives and friction-generating devices. This article is part of the theme issue 'Bioinspired materials and surfaces for green science and technology (part 2)'.